The role of France in strengthening science in Serbia and the Western Balkans: Between scientific cooperation and science diplomacy - Kolaković Aleksandra (Srpska Politička Misao)
France has a long tradition of cultural and scientific influence in the Balkan region, and historically especially in Serbia and in the countries formed on the territory of the former Yugoslavia (Kingdom of Serbs, Croats and Slovenes, Kingdom of Yugoslavia). The aforementioned influence, which followed its economic and political influence, was founded not only on the basis of the Alliance in the Great War (1914-1918), but primarily on the basis of the education and training of the Serbs and Balkans at the Sorbonne and at other French universities. After returning to their homeland, they not only occupied key positions in the state administration and reached ministerial positions, but also founded scientific disciplines and continued cooperation with their French professors and scientists. This historically long scientific cooperation, which showed elements of "science diplomacy", was also a foundation for creating France's scientific cooperation with Serbia, Montenegro, North Macedonia, Bosnia and Herzegovina and Albania (the countries of the Western Balkans, under which France also includes Kosovo*1 ). Through the analysis of available documents, press, interviews and statements of officials and diplomats, as well as scientists participating in joint projects, our main goal is to research the role of France in strengthening scientific cooperation in Serbia and the Western Balkans. Qualitative and quantitative analysis of the results of the "Pavle Savić" cooperation program, scientific cooperation in the Danube region and ES-Balk program, enable the observation of France's activities in the Balkans in the context of the scope of scientific diplomacy. Our research shows that since the Strategy for the Western Balkans (2019), France has been continuously committed to the development of political, economic and cultural cooperation with the countries in the Balkans, with more intensive scientific cooperation in accordance with the basic principles of France's science diplomacy strategy. It is observed that France insists on regional projects in the field of science, which contain a strong European component. Paper give recommendations for further cooperation in the field of science. The focus is on the special importance of the transfer of knowledge and the role of science in the framework of diplomacy, and therefore the role of France in the Balkans will also be research through this prism.